2006
DOI: 10.1097/01.jnen.0000229989.25171.aa
|View full text |Cite
|
Sign up to set email alerts
|

Paired Overexpression of ErbB3 and Sox10 in Pilocytic Astrocytoma

Abstract: Pilocytic astrocytoma (PA) is the most common glioma of childhood. Despite their relatively high incidence, the molecular mechanisms responsible for tumorigenesis and growth of PA are poorly understood. Previous in vitro studies in our laboratory showed that despite the absence of ErbB1, PA was sensitive to ErbB1 tyrosine kinase inhibitor gefitinib. To identify alternative targets of gefitinib in PA, we studied other members of the ErbB receptor tyrosine kinase family that have been identified in brain tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…Sox10 has in pilocytic astrocytomas been correlated with high expression of ErbB3 suggesting that Sox10 is driving the overexpression of ErbB3 which may result in induced cell proliferation (Addo-Yobo, et al, 2006). This finding is supported by the knowledge that Sox10 is regulating ErbB3 in neural crest cells during development (Britsch, et al, 2001).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Sox10 has in pilocytic astrocytomas been correlated with high expression of ErbB3 suggesting that Sox10 is driving the overexpression of ErbB3 which may result in induced cell proliferation (Addo-Yobo, et al, 2006). This finding is supported by the knowledge that Sox10 is regulating ErbB3 in neural crest cells during development (Britsch, et al, 2001).…”
supporting
confidence: 76%
“…Consistently with several other studies we have reported that Sox10 is expressed in both paediatric and adult gliomas and ependymomas with a higher expression in low grade tumours compared to high grade tumours (Addo-Yobo, et al, 2006;Bannykh, et al, 2006;Colin, et al, 2007;Ferletta, et al, 2007). On the contrary Schlierf et al found that when investigating the mRNA levels of Sox10 in glioma the expression levels were lower compared to adult brain (Schlierf, et al, 2007).…”
supporting
confidence: 70%
“…296 ERBB3 and brain cancer-ERBB3 and the transcription factor SOX10, which regulates ERBB3 directly or indirectly in neural tissue, are notably overexpressed in pilocytic astrocytoma (a common childhood glioma), compared with other pediatric brain tumors. 297,298 Since SOX10 is an embryonic neural regulator of ERBB3, these childhood neoplasms may reflect a dysregulated developmental pathway. SOX10 was expressed in three-fourths of schwannomas, and in relatively differentiated neoplasms, for example in schwann-like cells of neuroblastoma (all ganglioneuromas and some stage IV neuroblastomas), correlated with widespread expression of ERBB3.…”
Section: Hematopoietic Neoplasmsmentioning
confidence: 99%
“…The most prominent signal transduction pathways implicated to mediate these growth and suppressive signals include the Janusactivated kinase/Stat, phosphatidylinositol 3-kinase/Akt, and Ras/ extracellular signal-regulated kinase and protein kinase Ca pathways (2). In pediatric brain tumors, research mainly focused on the potential involvement of specific protein kinases such as epidermal growth factor receptor, platelet-derived growth factor receptor, phosphatidylinositol 3-kinase, and Janus-activated kinase in cell proliferation and survival (3)(4)(5)(6)(7)(8). The overall complexity and coregulation of the various signaling networks, however, has not been unraveled yet.…”
Section: Introductionmentioning
confidence: 99%